PENGARUH KOORDINASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN LAMPUNG BARAT - . Malik; Yadi Fahrozi (e-JKPP, 2019)
The problems in this study are: (1) Does coordination have a positive effect on employee performance at the West Lampung District Legislative Council Secretariat (DPRD), (2) Does work motivation have a positive effect on employee performance at the Regional Representative Council Secretariat (DPRD) of the Regency West Lampung, (3) Does coordination and work motivation affect employee performance at the Secretariat of the Regional People's Representative Council (DPRD) West Lampung Regency.In this study, using an explanatory survey method, by analyzing the influence of the coordination variable and work motivation as the independent variable on employee performance as the dependent variable. Researchers use a research approach in accordance with the objectives to be achieved, namely in addition to describing and describing the empirical facts found in the field, they will also carry out a qualitative analysis between the independent variables and the dependent variable.The results showed that there was a significant influence both coordination and work motivation on employee performance partially as well as, coordination and work motivation together had an effect on employee performance at the Secretariat of the Regional People's Representative Council (DPRD) West Lampung Regency. According to the results of the assessment criteria, the coordination variables and employee motivation on employee performance are in the good enough category, but not yet optimal. This is because there are other variables that influence but are not researched